Effects of pharmacological inhibition of fatty acid amide hydrolase on corticosterone release: a systematic review of preclinical studies - Christina F. Pereira; Isabelle Boileau; Stefan Kloiber (Discover Mental Health)
Abstract Psychiatric conditions are often linked to dysfunction of the Hypothalamic–Pituitary–Adrenal (HPA) axis. The Endocannabinoid System (ECS) plays a significant role in stress and anxiety and interacts with the HPA axis. The ECS metabolizing enzyme, Fatty Acid Amide Hydrolase (FAAH), may be integral for HPA axis response to stress by reducing levels of the endocannabinoid anandamide (AEA). However, there is conflicting evidence regarding the effects of FAAH inhibition on stress-related hormone changes, and no comprehensive evaluation of this literature exists. This review aims to synthesize the literature on the impact of pharmacological FAAH inhibition on corticosterone levels in rodents. A systematic search of PubMed/MEDLINE, APA PsychInfo, and Embase up to July 2024 was conducted. Articles reporting the effects of FAAH inhibition on corticosterone levels in rodents were included. Risk of Bias was assessed using SYRCLE’s Risk of Bias tool. This review included 21 articles. FAAH inhibition showed limited effects depending on type of FAAH inhibitor, stress exposure, and rodent age. Selective FAAH inhibition did not significantly affect corticosterone levels in the absence of stress and showed minimal effects following acute stress. After chronic stress, these compounds showed more pronounced effects, reducing corticosterone in 40% of studies. Limited studies employing flavonoid-based and dual FAAH/TRPV1 inhibitors suggested blunted corticosterone after acute, but not chronic stress. This review found that FAAH inhibition has inconsistent effects on corticosterone regulation, highlighting the complex and context-dependent role of FAAH inhibition in modulating stress hormone responses, warranting further investigation to clarify its therapeutic potential in stress-related disorders.